PENGARUH FIRM MASSAGE COUNTERPRESSURE TERHADAP PENGURANGAN INTENSITAS NYERI PADA PERCEPATAN KALA I BAGI IBU INPARTU DI KLINIK BABARSARI MEDAN TUNTUNGAN TAHUN 2015 - Jujuren Sitepu; Betty Mangkuji (Universitas Methodist Indonesia, 2018)
The maternal mortality rate was 359 / 100,000 births, in North Sumatra 188 / 100,000 births and the city of Medan were 152 mothers who died from 206,990 births. The causes of death are bleeding, eclampsia, infection, congestion and others and causes of death. The cause of congestion is labor pain. Pain during labor is a physiological condition that is commonly experienced by almost all women giving birth. Handling labor pain firm counterpressure massage. The aim of the study was to determine the effect of firm massage counter pressure on reducing pain intensity and acceleration in period I. This was a quantitative observational study using a quasi-experimental design of the entire population that gave birth to the Babar Sari clinic and the Helen Clinic in Medan with benefits of 30 people. Data were analyzed using computer software and tested its usefulness using paired t-test. The result of the normality test is the influence of massege on the level of pain and acceleration when I with the value of p value = 0.237> p value 0.05, which means that normal distribution is continued and the paired t-test is obtained with a p value = 0,000 <0.05. There is the influence of firm massage counter pressure on reducing pain intensity and also influencing the acceleration of the first period with values p value = 0.041 <0.05. Suggestion that firm massage counter pressure be protected in midwifery care at the time.